Role cognition of assigned nurses supporting Hubei Province in the fight against COVID-19 in China: a hermeneutic phenomenological study - Zhang, Xu; Wang, Yaqian; Chen, Yuanyuan; Yang, Hailing; Luan, Xiaorong (Frontiers in Psychology, 2024)
Aims: During the epidemic of COVID-19, nurses played a crucial role in clinical treatment. As a special group, front-line nurses, especially those assigned to support Hubei province to fight COVID-19, who came from different provinces in China from February to April 2020, had valuable experiences about taking care of these COVID-19 patients and role cognition. Therefore, our purpose is to explore the real coping experience and role cognition of front-line nurses under the novel corona virus outbreak so as to provide relevant experience references for society and managers in the face of such major public health emergencies in the future. Design: This qualitative study was performed using the phenomenological hermeneutics method. Method: This is a qualitative phenomenological study. Semi-structured in-depth interviews were used to collect data. The interviewees were 53 front-line nurses who assisted and supported the fight against COVID-19 in Hubei Province during the COVID-19 epidemic. Data were collected through individual online interviews and telephone interviews using a semi-structured interview during March 2020. The COREQ guidance was used for reporting this study. Results: Finding revealed that front-line nurses assisting in fighting COVID-19 developed a context-specific role cognition of their work and contribution to society. Qualitative analysis of the data revealed 15 sub-categories and 5 main categories. 5 themes represented the different roles nurses identified. The roles included expectations, conflicts, adaptation, emotions and flow of blessing. Belief in getting better, a sense of honor, and training could help them reduce feeling conflict in this role and adapt more quickly. Discussion: This article discusses the real coping experience and role cognition of front-line nurses under the novel corona virus epidemic, and provides relevant experience reference for society and managers to face such major public health emergencies in the future. This study makes a significant contribution to the literature because it demonstrates how non-local nurses sent to Hubei to work perceived their roles as part of a larger narrative of patriotism, duty, solidarity, and hope.